2016
DOI: 10.1016/j.psychres.2016.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect predicts social functioning across schizophrenia and bipolar disorder: Findings from an integrated data analysis

Abstract: Most people with a serious mental illness experience significant functional impairment despite ongoing pharmacological treatment. Thus, in order to improve outcomes, a better understanding of functional predictors is needed. This study examined negative affect, a construct comprised of negative emotional experience, as a predictor of social functioning across serious mental illnesses. One hundred twenty-seven participants with schizophrenia, 113 with schizoaffective disorder, 22 with psychotic disorder not oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 111 publications
(120 reference statements)
2
27
0
Order By: Relevance
“…Many of the studies we cite include schizoaffective patients, but there has been little attempt to differentiate NA in schizoaffective disorder and schizophrenia, aside of the obvious higher incidence of NA (depressive symptoms) in schizoaffective disorder. 64 Although we see the proposed GABAergic mechanisms of vulnerability and NA as transdiagnostic, most of the relevant research has occurred in schizophrenia; hence, our focus.…”
Section: A Model Of Vulnerability and Negative Affectmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the studies we cite include schizoaffective patients, but there has been little attempt to differentiate NA in schizoaffective disorder and schizophrenia, aside of the obvious higher incidence of NA (depressive symptoms) in schizoaffective disorder. 64 Although we see the proposed GABAergic mechanisms of vulnerability and NA as transdiagnostic, most of the relevant research has occurred in schizophrenia; hence, our focus.…”
Section: A Model Of Vulnerability and Negative Affectmentioning
confidence: 99%
“…[65][66][67] Depression occurs in 30%-50% of schizophrenia patients, 68,69 and social phobia in 13%-36% of schizophrenia cases, [70][71][72] with as many as 60% of patients experiencing some form of social anxiety. 73 NA is associated with poor social functioning and poor quality of life, after controlling for positive and negative symptoms, 32,64,74,75 suggesting that it is an important target for interventions.…”
Section: Negative Affect and Schizophrenia Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between affect and social functioning has been investigated, in particular using clinical samples. It has been found that in young adults and adults (18–68 years old) PA has been positively related to social functioning scores [ 22 – 24 ] whereas NA has been related negatively [ 25 – 27 ]. The very few studies examining this relationship in community samples have focused on young adults and adults (18–35 years old).…”
Section: Introductionmentioning
confidence: 99%
“…It is also acknowledged that our patient sample is quite heterogeneous in terms of diagnosis, where we have included both affective and nonaffective psychosis. Negative symptoms can be challenging to study in affective psychosis populations; however, negative symptoms have been reliably observed in patients with affective psychosis (Grove et al, 2016;Guessoum, Le Strat, Dubertret, & Mallet, 2020;SauvĂ©, Brodeur, Shah, & Lepage, 2019;Strauss et al, 2018;Strauss, Vertinski, Vogel, Ringdahl, & Allen, 2016). We have also previously controlled for diagnosis in our brain imaging studies of negative symptoms, finding that results are not altered (Makowski et al, 2017;.…”
Section: Discussionmentioning
confidence: 99%